Using Audio Visual Media to Improve Muhadatsah Learning for Class VII Students at Mts Negeri 1 Tapanuli Tengah - Salamuddin, Salamuddin; Simamora, Elida Rahmi (ISTAWA, 2022)
This study aims to analyze: 1) teacher planning in the use of audio-visual media in the seventh grade Muhadatsah learning at MTs Negeri 1 Tapanuli Tengah, 2) the use of audio-visual media to improve Muhadatsah learning in seventh grade students at MTs Negeri 1 Tapanuli Tengah, 3) student learning outcomes by using audio-visual media in learning Muhadatsah class VII MTs Negeri 1 Tapanuli Tengah.This research was carried out with a qualitative approach, because the focus of the research is how to use audio-visual media in Muhadatsah learning, the reason the researcher uses this type of qualitative research is because the problem is not clear, holistic, complex, dynamic, and full of meaning so it is impossible for data on social situations to be captured. with instruments such as tests, questionnaires, interview guidelines. The results showed that: 1) In planning the use of audio-visual media, the teacher paid attention to the competency standards contained in the 2013 Curriculum. By paying attention to the existing competency standards, the material used did not deviate from the existing signs. Teachers also pay attention to the availability of supporting facilities and infrastructure so that the learning process can run smoothly and in accordance with the objectives. 2) Implementation of the use of audio-visual media in learning has a positive impact on students. Students get a new learning atmosphere, the classroom atmosphere becomes more interactive, learning becomes interesting, students become more enthusiastic and more motivated to take part in learning. 3) Learning outcomes have increased after the teacher uses audio-visual media. The increase in learning outcomes is also followed by an increase in the absorption of students in receiving lessons. As well as increasing the percentage of Minimum Completeness Criteria (KKM).